Clinical and radiological diagnosis Of progressive pseudorheumatoid dysplasia in two sisters with severe polyarthropathy - Kaya, A; Ozgocmen, S; Kiris, A; Ciftci, I (Springer London Ltd, 2005)
The aim of this case report is to describe unusual cases of progressive pseudorheumatoid dysplasia (PPD) affecting the axial skeleton and peripheral joints and to stress the importance of examining the entire skeleton for definite diagnosis and the importance of rehabilitation interventions. PPD is a rare familial disease characterized by generalized bone-cartilage dysplasia, progressive arthropathy, and platyspondyly. PPD presents as spondyloepiphyseal dysplasia (SED) tarda with progressive arthropathy and progressive pseudo rheumatoid arthritis of childhood and is described as a specific autosomal recessive subtype of SED. Two sisters, 18 and 16 years old, with low back pain and polyarthritis are presented. Radiographic and magnetic resonance imaging of the cases revealed typical features characteristic for PPD-like platyspondyly, multiple intravertebral herniations, changes in metaphyses and,epiphysis, and megaostrigonum. Consequently, PPD is a rare disease of childhood and should be kept in mind in the differential diagnosis of juvenile idiopathic arthritis to prevent delayed diagnosis and to begin rehabilitation interventions early. It is essential to carefully examine the entire body, particularly the axial skeleton, and to perform radiological evaluation of the spine. These illustrative cases serve to remind physicians to examine the entire skeleton and not to concentrate only on branches but also on the trunk.
Keywords: magnetic resonance; osteochondrodysplasias; progressive pseudorheumatoid dysplasia